Stimulate Smooth Motoric Development in Preschool Children By Using Educational Game Tools - Dian Vita Sari; Fatmawati; Bukhari (Babali Nursing Research, 2022)
Introduction: The development of smooth motoric, language, and interact to adapted in social are the growth of preschool aged children involves aggressive. Children’s movements that use a small muscles or only certain parts of the body smooth motoric is process in growth. The growth of this aspect can be stimulated, which kind of the use of Educational Game Tools (EGT). The purpose of this research was to identify the usefulness of using educational games equipment to stimulate smooth motoric growth in preschool children at Srikandi Kindergarten, Lhokseumawe. Methods: The method used in this research was Quasi-experimental Research. The technique of this study took the illustration by using the random sampling technique, with a total of 31 respondents who were given stimulation at that time. The data from this study were processed by using a dependent T-test of the variables of educational games and smooth motoric development in preschool children. Results: The results of this study showed that the use of educational games is effective for stimulating smooth motoric development in preschool children with a p-value = 0.000 < (0.05). Conclusion: The study can be concluded that children aged 4-5 years have questionable smooth motor development and irregularities before being given Educational Game Tools (EGT) stimulation. It is suggested to parents of respondents to use educational game tools to stimulate motoric development in children according to their developmental age.